Anne Frank, Beyond the Diary : A Photographic Remembrance - Rol, Ruud van der and Verhoeven, Rian; Translated by Langham, Tony and Peters, Plym (Londom Scholastic Inc, 1993)
Photographs, illustrations, and maps accompany historical essays, diary excerpts, and interviews, providing an insight to Anne Frank and the massive upheaval which tore apart her world.
Including Illustrations,Index and Chronology
With an Introduction by Quindlen, Anna
Keywords: Jews -- Netherlands--Amsterdam -- Holocaust, Jewish--(1939-1945)